Effect of probiotic administration on the intestinal microbiota, current knowledge and potential applications - de Moreno, Maria Alejandra (2014)
Although it is now known that the human body is colonized by a wide variety of microbial populations in different parts (such as the mouth, pharynx and respiratory system, the skin, the gastro- and urogenital tracts), many effects of the complex interactions between the human host and microbial symbionts are still not completely understood. The dysbiosis of the gastrointestinal tract microbiota is considered to be one of the most important contributing factors in the development of many gastrointestinal diseases such as inflammatory bowel disease, irritable bowel syndrome and colorectal cancer, as well as systemic diseases like obesity, diabetes, atherosclerosis and non-alcoholic fatty liver disease. Fecal microbial transplantations appear to be promising therapies for dysbiosis-associated diseases; however, probiotic microorganisms have been growing in popularity due to increasing numbers of studies proving that certain strains present health promoting properties, among them the beneficial balance of the intestinal microbiota. Inflammatory bowel diseases and obesity are the pathologies in which there are more studies showing this beneficial association using animal models and even in human clinical trials. In this review, the association of the human gut microbiota and human health will be discussed along with the benefits that probiotics can confer on this symbiotic activity and on the prevention or treatment of associated diseases.